Enzymatic Deinking Using Thermostable And Alkaliphilic Endoglucanase Of Indigenous Bacteria - Dayang Syahreeny, Abang Mustafa (Universiti Malaysia Sarawak (UNIMAS), 2010)
The best endoglucanase producer has been successfully isolated and identified from Paku Hot Springs based on 'halo' fonnation during Congo red screening on minimal salt media containing 1% (w/v) of carboxymethyIceIlulose. Molecular approach targeting the conserved region of 16S rRNA bacterial strain performed was unable to further conf'inn initial morphological and biochemical tests results of the isolate which was identified as Klebsiella spp. An optimal condition for endoglucanase secretion by Klebsiella spp. was determined successful at pH 7.2 and 37°C after 9 hours of incubation using 5% of inoculums. The crude endogucanase activity was determined using ONS method and prolein content was determined via Bradford method. Native PAGE and SOS PAGE were performed to detennine crude endoglucanase enzymatic activity and molecular weight of crude endoglucanase, respectively. Km, VNX K.:•• values of crude endoglucanase were 0.7765 mg/ml, 0.6242 unitslml and 1.6 S·I, respectively. Enzymatic deinking of Mi xed Ofiice Wastepaper (MOW) using 50% enzyme of total reaction volume shows enhancement in brightness but deinking ability was not determined.